DIAGNOSTIC QUESTION STRUCTURAL MODELS OF CAUSALITY DURING INJURY INFLICTION - Voronov, V.T. (World of Medicine and Biology, 2016)
On the example of cause- system one-level models of regular communication (determination) examined the object determinants - the cause and conditions - as elements of structure system of the full causes of injury. Using retrospective cause and system modeling defined cancellation these properties objective determinants that act diagnostic criteria causal relationships and relations conditionality in traumatic process.